Using the Balanced Scorecard Method, Evaluate the Nurses' Success in Raising Service Quality - Prayoga, Dicky (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Performance appraisal can provide information about needs effectiveness of employee training and development and can provide information regarding design employee compensation. The purpose of this study was to analyze the performance of nurses and service quality at the Anmarsu Hospice Care Mental Hospital. The research method used in this study uses a qualitative approach descriptive, with the collection of data sources obtained primarily by interviews. The analysis used in this study uses techniques analysis Fill in using a measuring tool Balanced Scorecard. Based on the results of the calculations score regularly whole, obtained the total score is 282 points which means that Anmarsu Hospice Care Mental Hospital has a very good approach in measuring organizational performance.